Environmental and health risks posed to children by artisanal gold mining: A systematic review. (February 2022) - Allan-Blitz, Lao-Tzu; Goldfine, Charlotte; Erickson, Timothy B
There are an estimated 5 million children working in artisanal and small-scale gold mines worldwide; however, the hazards are poorly characterized and often underreported. We systematically reviewed the literature on reports of hazards among children as a consequence of such activities through PubMed database using pre-defined search terms. We identified 113 articles published between 1984 and 2021 from 31 countries. Toxicological hazards were reported in 91 articles, including mercury, lead, and arsenic. Infectious hazards, noted in 18 articles, included malaria, cholera, and hepatitis. Six articles reported occupational hazards, including malnutrition, heat stroke, and reactive airway disease. Three articles reported traumatic hazards, including cave-ins, burns, animal attacks, falls, and weapon-inflected wounds. Those findings likely indicate a profound underreporting of the prevalence and consequences of such hazards among children. More work is needed both to characterize the burdens of those hazards and to address the underlying drivers of child labor in those settings.